Hepatic biotransformation of non-psychotropic phytocannabinoids and activity screening on cytochromes P450 and UDP-glucuronosyltransferases - Havlasek, Jakub; Vrba, Jiri; Zatloukalova, Martina; Papouskova, Barbora; Modriansky, Martin; Storch, Jan; Vacek, Jan (Toxicology and applied pharmacology, 2023)
This study examined the biotransformation of phytocannabinoids in human hepatocytes. The susceptibility of the tested compounds to transformations in hepatocytes exhibited the following hierarchy: cannabinol (CBN) > cannabigerol (CBG) > cannabichromene (CBC) > cannabidiol (CBD). Biotransformation included hydroxylation, oxidation to a carboxylic acid, dehydrogenation, hydrogenation, dehydration, loss/shortening of alkyl, glucuronidation and sulfation. CBN was primarily metabolized by oxidation of a methyl to a carboxylic acid group, while CBD, CBG and CBC were preferentially metabolized by direct glucuronidation. The study also screened for the activity of recombinant human cytochromes P450 (CYPs) and UDP-glucuronosyltransferases (UGTs), which could catalyze the hydroxylation and glucuronidation of the tested compounds, respectively. We found that CBD was hydroxylated mainly by CYPs 2C8, 2C19, 2D6; CBN by 1A2, 2C9, 2C19 and 2D6; and CBG by 2B6, 2C9, 2C19 and 2D6. CBC exhibited higher susceptibility to CYP-mediated transformation than the other tested compounds, mainly with CYPs 1A2, 2B6, 2C8, 2C19, 2D6 and 3A4 being involved. Further, CBD was primarily glucuronidated by UGTs 1A3, 1A7, 1A8, 1A9 and 2B7; CBN by 1A7, 1A8, 1A9 and 2B7; CBG by 1A3, 1A7, 1A8, 1A9, 2B4, 2B7 and 2B17; and the glucuronidation of CBC was catalyzed by UGTs 1A1, 1A8, 1A9 and 2B7.
Keywords: kyseliny karboxylové; lidé; Biotransformation; Glucuronosyltransferase; glukuronosyltransferasa; Uridine Diphosphate; systém (enzymů) cytochromů P-450; biotransformace; Cytochrome P-450 Enzyme System; Humans; Carboxylic Acids; Microsomes, Liver; jaterní mikrozomy; uridindifosfát